Evaluating the diagnostic capacity of a single-question neuropathy screen (SQNS) in HIV positive Zambian adults. Issue 12 (11th June 2010) - Kandiah, Prem A; Atadzhanov, Masharip; Kvalsund, Michelle P; Birbeck, Gretchen L
Abstract : A single-question neuropathy screen (SQNS) is routinely included in the enrolment data for people commencing antiretroviral therapy in publically funded clinics in Zambia. The authors assessed the sensitivity, specificity, positive and negative predictive value of this SQNS against the Brief Peripheral Neuropathy Screen (BPSN) in detecting HIV-associated sensory neuropathy in patients recruited from a rural and an urban hospital in Zambia. The SQNS was asked followed by conduct of the BPNS by the neurology resident assisted by a Zambian healthcare worker/translator. 77 patients (48 (62.3%) urban and 29 (37.7%) rural) were enrolled. 13 subjects were excluded due to altered mental status. The mean age was 33.7 years (range 15–53 years; SD±7.81). The SQNS was 95.7% sensitive and 80.0% specific, with 88.2% positive predictive value and 92.3% negative predictive value. Age, geographical location, gender and WHO stage were all unrelated to the performance of the SQNS (p>0.05). Despite its reliance on symptoms alone, this study suggests that the SQNS may be a valid research tool for identifying HIV-associated neuropathy among advanced stage HIV patients in Zambia.